Cosmology - Baumann, Daniel, 1978- (2022)
"The author-a leading theoretical cosmologist-expands on his widely acclaimed lecture notes in this self-contained textbook, suitable for the advanced undergraduate or starting graduate level. Presenting the key theoretical foundations of cosmology and describing the observations that have turned the subject into a precision science, the author keeps the student in mind on every page by explaining concepts step-by-step, in an approachable manner. After describing the dynamics of the homogeneous universe, the book traces the evolution of small density fluctuations, which were created quantum-mechanically during inflation and are today observed in the cosmic microwave background and the large-scale structure of the universe. The book is ideally suited as a course companion or for self-study. With all necessary background material covered, students have everything they need to establish an unrivalled understanding of the subject. Complete with many worked examples, figures, and homework problems, this textbook is a definitive resource for advanced students in physics, astronomy and applied mathematics"--
Includes bibliographical references and index.
Keywords: Cosmology; SCIENCE / Space Science / Cosmology